Kinetics and Mechanism of Oxidation of Ethylglcol by Alkaline Hexacyanoferrate(III) Ions - Goel, Anjali; Verma, G.R.; Singh, H.S. (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of ethylglycol by hexacyanoferrate(III) ions in aqueous alkaline medium has been reported. The reaction is first order with respect to hydroxide ion and substrate. The reaction also shows nearly first order kinetics at lower concentrations of hexacyanoferrate(III) ions which tends towards zero order at its higher concentrations. The course of reaction has been considered to proceed through the formation of activated complex between KFe(CN)2–6 and substrate anion which decomposes into product and KFe(CN)3–6.